Analysis of disulphide bond linkage between CoA and protein cysteine thiols during sporulation and in spores of Bacillus species. Issue 23 (18th November 2020) - Zhyvoloup, Alexander; Yu, Bess Yi Kun; Baković, Jovana; Davis-Lunn, Mathew; Tossounian, Maria-Armineh; Thomas, Naam; Tsuchiya, Yugo; Peak-Chew, Sew Yeu; Wigneshweraraj, Sivaramesh; Filonenko, Valeriy; Skehel, Mark; Setlow, Peter; et al.
ABSTRACT: Spores of Bacillus species have novel properties, which allow them to lie dormant for years and then germinate under favourable conditions. In the current work, the role of a key metabolic integrator, coenzyme A (CoA), in redox regulation of growing cells and during spore formation in Bacillus megaterium and Bacillus subtilis is studied. Exposing these growing cells to oxidising agents or carbon deprivation resulted in extensive covalent protein modification by CoA (termed protein CoAlation), through disulphide bond formation between the CoA thiol group and a protein cysteine. Significant protein CoAlation was observed during sporulation of B. megaterium, and increased largely in parallel with loss of metabolism in spores. Mass spectrometric analysis identified four CoAlated proteins in B. subtilis spores as well as one CoAlated protein in growing B. megaterium cells. All five of these proteins have been identified as moderately abundant in spores. Based on these findings and published studies, protein CoAlation might be involved in facilitating establishment of spores' metabolic dormancy, and/or protecting sensitive sulfhydryl groups of spore enzymes. Abstract : Analysis of protein CoAlation during sporulation and in spores of Bacillus species.